Arterial stiffness and microvascular disease in type 2 diabetes. (29th August 2020) - Antonopoulos, Alexios S.; Siasos, Gerasimos; Oikonomou, Evangelos; Gouliopoulos, Nikolaos; Konsola, Theodosia; Tsigkou, Vasiliki; Moschos, Marilita; Tentolouris, Nikolaos; Kassi, Eva; Paschou, Stavroula A.; Thanopoulou, Anastasia; Vavuranakis, Manolis; et al.
Abstract: Background: The clustering of arterial stiffness with microvascular disease (MD) and their effects on the clinical outcome of patients with type 2 diabetes (T2D) remains not fully clarified. Methods: In a prospective study of 414 patients with T2D, we investigated the prognostic value of arterial stiffness and MD for clinical outcomes. Participants were assessed for the presence of MD ( ie diabetic retinopathy, nephropathy and neuropathy) and arterial stiffness by pulse wave velocity (PWV) and followed‐up for a median of 30 (range 1‐60) months. The primary endpoint of the study was the composite endpoint of major adverse cardiovascular events, that is, cardiovascular and non‐cardiovascular mortality and non‐fatal myocardial infarction/stroke. Results: A total of 146 (35.3%) patients had evidence of MD at baseline. In cox regression models, MD and PWV were independently associated with the composite clinical endpoint; for MD hazard ratio (HR), 3.24, 95%CI, 1.10‐9.54, P =.032, and for PWV HR, 1.20, 95%CI, 1.06‐1.36, P =.004) after adjustment for traditional risk factors, and enhanced risk discrimination and reclassification. The subgroup of patients with MD and high PWV was associated with increased incidence of the composite clinical endpoint (20.9% vs 1.8% in those with no MD & low PWV, P =.001). Importantly, absence of MD at baseline was associated with no mortality events during the follow‐up period. PWV at baseline was not associated with MD progression during follow‐up. Conclusions: These findings support that screening for arterial stiffness and MD in the routine clinical assessment of patients with T2D may enhance prognostication and cardiovascular risk reclassification.